RESULTS OF THE EXPLORATORY TRAWL FISHING OFF CANNANORE BY THE INDO-NORWEGIAN PROJECT VESSELS - Kuthalingam, M D K; Chellam, A (Indian Journal of Fisheries, 2011)
The offshore fishery resources off Cannanore have been assessed from the exploratory trawling data of the Indo-Norwegian Project Vessels during the 3-year period, from 1963-’64 to 1965-’66. The total landings, catch rate and depth-wise distribution of the important categories of the trawler catches are presented. Observations on length, sex, and maturity stages of the more important species recorded in the trawl catches are given. Results of the qualitative and gross quantitative analyses of the food and feeding habits of 31 species of fishes and 3 species of prawns are also included